BIMBINGAN KONSELING ISLAM BAGI PASIEN RAWAT INAP DI RUMAH SAKIT ROEMANI MUHAMMADIYAH SEMARANG - Agus Riyadi; Abdullah Hadziq; Ali Murtadho (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2019)
The psychiatric conditions of patients being treated in hospitals vary so that physical, psychological, medical and spiritual services are needed for all patients. This shows the importance of holistic treatment including medical and non-medical actions which enable them to get motivation, entertainment, support, suggestions, empathy and various matters relating to the psychological aspects. This study is intended to reveal the importance and implementation of Islamic counselling at Roemani Muhammadiyah Hospital Semarang. As a qualitative field research, data were collected through free interviews, participant observation, and documentation. All data were analyzed by the phenomenological approach and descriptive analysis using the logic of induction, deduction, and reflection. The findings suggested that Islamic counseling is needed for inpatients because everyone always has four dimensions: biological or physical, psychological, social, and spiritual. These four dimensions are one unit that is interrelated to determine the quality of one’s health. The existing Islamic guidance and counseling has not yet implemented a system of professional counseling services. The form of all services provided to patients is almost just guidance service model such as giving prayer, motivation, worship, and advices so that there has not been implemented counseling services. Moreover, many Islamic counseling service officers at Roemani hospital in Muhammadiyah Semarang have not fully understood the stages that must be performed by a counselor in providing counseling services.